2019
DOI: 10.1155/2019/2647079
|View full text |Cite
|
Sign up to set email alerts
|

Integration of CTA in the Diagnostic Workup of New Onset Chest Pain in Clinical Practice

Abstract: Background. Recently, NICE guidelines recommend the use of computed tomographic angiography (CTA) as the first line of investigation for new onset chest pain. We sought to evaluate the impact of the integration of CTA in the diagnostic workup, as either a first- or second-line of investigation, in the clinical practice for patients presenting with new onset chest pain, with suspicion that it may be due to coronary artery disease (CAD). Method and Results. From 2014 to 2016, 208 outpatients (mean age 63.8 ± 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In line with this, CTCA also reduced the time from ED to ICA. Reduced functional testing has also been shown in other studies of CTCA in outpatients with chest pain 27,28 …”
Section: Discussionmentioning
confidence: 57%
“…In line with this, CTCA also reduced the time from ED to ICA. Reduced functional testing has also been shown in other studies of CTCA in outpatients with chest pain 27,28 …”
Section: Discussionmentioning
confidence: 57%
“…In this study, we found that a CCTA plus S-CMR strategy works very well in clinical practice. First, we can safely avoid unnecessary further examination in a significant proportion of CCS patients showing no or only minimal plaques at CCTA, confirming its high negative predictive value [ 18 ]. More importantly, for CCS patients with intermediate coronary plaques at CCTA, the strategy of adding S-CMR appears to be effective, leading us to refine the selection of patients needing ICA and coronary revascularization, who in our study population were as many as a quarter of the patients.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, in the last years, advanced imaging modalities have been proposed for the evaluation of CAD: while cardiac computed tomography (CCT) use has been recommended in the last ESC guidelines [ 10 , 11 ] and National Institute for Health and Care Excellence (NICE) for younger patients with chest pain and low pretest probability of CAD, due to its greater anatomic insights and high negative predictive value (NPV) [ 15 ], cardiac magnetic resonance could be preferred for prognostic purposes in ACS and CCS [ 16 ]. In fact, in a cohort of 206 patients, the application of CCT, as first- or second-line investigation, allowed to spare 42.6% unnecessary invasive coronary angiography (ICA) and 63.7% of additional functional test (when used as first-line exam) [ 17 ]. However, CCT pitfalls still remain high costs and have low availability and a need of a specific trained team of operators and clinicians.…”
Section: Cad Diagnosismentioning
confidence: 99%